1990
DOI: 10.1002/1098-108x(199009)9:5<493::aid-eat2260090504>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Body image dissatisfaction and disordered eating in lesbian college students

Abstract: Lesbian subcultures have been described to downplay the importance of physical attractiveness and to challenge culturally prescribed beauty ideals. Within this context, one might argue that lesbians should be more accepting of their bodies and less likely to engage in disordered eating, than would heterosexual women. The relationship between sexual orientation and body esteem has not been examined empirically yet. This study compared 30 lesbian undergraduates and 52 heterosexual undergraduates on measures of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 9 publications
4
57
0
Order By: Relevance
“…The sample of homosexual females showed lower body dissatisfaction than heterosexuals, even though they were not less likely to report dieting, binge eating or unhealthy weight control behaviors (French et al, 1996). Lesbian subcultures have been described to downplay the importance of physical attractiveness and traditional ideals of beauty (Striegel- Moore, 1990). Within this context, one hypothesis has been that lesbians generally do not suffer from body image problems or disordered eating because they are not vulnerable to cultural pressures to be thin as most heterosexual women do (Brown, 1987).…”
Section: Sexual Orientation and Eating Disorders In Female Populationsupporting
confidence: 65%
See 2 more Smart Citations
“…The sample of homosexual females showed lower body dissatisfaction than heterosexuals, even though they were not less likely to report dieting, binge eating or unhealthy weight control behaviors (French et al, 1996). Lesbian subcultures have been described to downplay the importance of physical attractiveness and traditional ideals of beauty (Striegel- Moore, 1990). Within this context, one hypothesis has been that lesbians generally do not suffer from body image problems or disordered eating because they are not vulnerable to cultural pressures to be thin as most heterosexual women do (Brown, 1987).…”
Section: Sexual Orientation and Eating Disorders In Female Populationsupporting
confidence: 65%
“…Other studies, conversely, have found no major differences between hetero-and homosexual women concerning body dissatisfaction (Beren et al, 1996;Striegel-Moore et al, 1990), with regard to the presence of dysfunctional eating attitudes and behaviors (Streigel-Moore et al, 1990;Beren et al, 1996;Share & Mintz, 2002;Moore & Keel, 2003) or in rates of eating disorders (French et al, 1996). For example, Heffernan (1996) reported that lesbians were not significantly different from heterosexual women in attitudes concerning body weight and appearance or dieting.…”
Section: Sexual Orientation and Eating Disorders In Female Populationmentioning
confidence: 83%
See 1 more Smart Citation
“…Other research has found comparable levels of body dissatisfaction and disordered eating between groups of lesbian and heterosexual women (e.g., Beren et al 1996;Brand et al 1992;Striegel-Moore et al 1990). Morrison et al's (2004) meta-analysis showed no reliable difference in body dissatisfaction between lesbian and heterosexual women.…”
Section: Objectification Theory and Gendermentioning
confidence: 99%
“…However, little research has examined the relationship between sexual orientation and eating behaviors (IOM, 2011). With regard to binge eating specifically, research suggests that LB women are more likely to report binge eating compared to heterosexual women Heffernan, 1994;Striegel-Moore, Tucker, & Hsu, 1990). In fact, based on results of the Lesbian Healthcare Survey, 68% of lesbian women reported overeating "sometimes" or "often" (Bradford, Ryan, & Rothblum, 1994).…”
mentioning
confidence: 99%